The Acetylcholine-Activated Potassium Current Inhibitor XAF-1407 Terminates Persistent Atrial Fibrillation in Goats - Sobota, Vladimír; Gatta, Giulia; van Hunnik, Arne; van Tuijn, Iris; Kuiper, Marion; Milnes, James; Jespersen, Thomas; Schotten, Ulrich; Verheule, Sander (Frontiers in Pharmacology, 2021)
Aims: The acetylcholine-activated inward rectifier potassium current (IKACh) has been proposed as an atrial-selective target for the treatment of atrial fibrillation (AF). Using a novel selective IKACh inhibitor XAF-1407, the study investigates the effect of IKACh inhibition in goats with pacing-induced, short-term AF. Methods: Ten goats (57 ± 5 kg) were instrumented with pericardial electrodes. Electrophysiological parameters were assessed at baseline and during intravenous infusion of XAF-1407 (0.3, 3.0 mg/kg) in conscious animals before and after 2 days of electrically induced AF. Following a further 2 weeks of sustained AF, cardioversion was attempted with either XAF-1407 (0.3 followed by 3 mg/kg) or with vernakalant (3.7 followed by 4.5 mg/kg), an antiarrhythmic drug that inhibits the fast sodium current and several potassium currents. During a final open chest experiment, 249 unipolar electrograms were recorded on each atrium to construct activation patterns and AF cardioversion was attempted with XAF-1407. Results: XAF-1407 prolonged atrial effective refractory period by 36 ms (45%) and 71 ms (87%) (0.3 and 3.0 mg/kg, respectively; pacing cycle length 400 ms, 2 days of AF-induced remodeling) and showed higher cardioversion efficacy than vernakalant (8/9 vs. 5/9). XAF-1407 caused a minor decrease in the number of waves per AF cycle in the last seconds prior to cardioversion. Administration of XAF-1407 was associated with a modest increase in QTc (<10%). No ventricular proarrhythmic events were observed. Conclusion: XAF-1407 showed an antiarrhythmic effect in a goat model of AF. The study indicates that IKACh represents an interesting therapeutic target for treatment of AF. To assess the efficacy of XAF-1407 in later time points of AF-induced remodeling, follow-up studies with longer period of AF maintenance would be necessary.